Characterization of the functional interactions of plastidial starch phosphorylase and starch branching enzymes from rice endosperm during reserve starch biosynthesis. (November 2017) - Nakamura, Yasunori; Ono, Masami; Sawada, Takayuki; Crofts, Naoko; Fujita, Naoko; Steup, Martin
Highlights: Biochemical interactions of rice Pho1 and BE were characterized. Pho1 can efficiently synthesize branched glucans by forming the hetero-dimer with either of BE isoforms. Pho1 is capable of de novo synthesis of linear dextrins from maltose. Pho1 might play essential roles in the initial process of starch biosynthesis in developing rice endosperm. Abstract: Functional interactions of plastidial phosphorylase (Pho1) and starch branching enzymes (BEs) from the developing rice endosperm are the focus of this study. In the presence of both Pho1 and BE, the same branched primer molecule is elongated and further branched almost simultaneously even at very low glucan concentrations present in the purified enzyme preparations. By contrast, in the absence of any BE, glucans are not, to any significant extent, elongated by Pho1. Based on our in vitro data, in the developing rice endosperm, Pho1 appears to be weakly associated with any of the BE isozymes. By using fluorophore-labeled malto-oligosaccharides, we identified maltose as the smallest possible primer for elongation by Pho1. Linear dextrins act as carbohydrate substrates for BEs. By functionally interacting with a BE, Pho1 performs two essential functions during the initiation of starch biosynthesis in the rice endosperm: First, it elongates maltodextrins up to a degree of polymerization of at least 60. Second, by closely interacting with BEs, Pho1 is able to elongate branched glucans efficiently and thereby synthesizes branched carbohydrates essential for the initiation of amylopectin biosynthesis.